Penguatan Pendidikan Karakter melalui Literasi Digital di Sekolah Dasar - Nurul Nisa; Noviani Arum Sari Nur Hidayat; Yona Wahyuningsih (Departement of Mathematics Education, 2023)
In the era of digitalization, education must always be improved and improved, so that it can produce the expected generations. One way is to provide character education. The purpose of writing this article is to examine how digital literacy is used to strengthen character education. The method used in this research is a literature study research method that is carried out qualitatively or descriptively of literature obtained through the literacy process of various sources. The results of the research show that increasing character education through digital literacy can be a strategy to face the 4.0 era. Through digital literacy, efforts to strengthen the 5 basic characters can be grown and developed systematically and effectively